PENGARUH SUHU BAHAN BAKAR TERHADAP EMISI GAS BUANG PADA MESIN BENSIN 1800 cc - Yuniarto Agus Winoko; Santoso (Politeknik Negeri Malang, 2020)
The perfect combustion process can occur if the high compression pressure, proper ignition time, and suitable fuel air mixture. Suitable fuel air mixture can be obtained by heating the fuel to reduce its viscosity so the mixture is more homogeneous. Fuel heating can be done in various ways, such as by utilizing the heat of radiator water coming out of the engine. The purpose of the study is determine effect of the fuel heating to exhaust emission of gasoline engine 1800cc. The study uses experimental with the variable used pertamax with temperature 40°, 50°, 60°, and 70°. The dependent variable in the study is exhaust emission of gasoline engine. The results of the study indicate that fuel heating affects exhaust emissions. Temperature that affects the exhaust gas emissions at 60o C with the use of pertamax fuel.